Revolutionizing Code: The Role of AI in Software Engineering - Rahul Sanjay Panchal (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Information regarding artificial intelligence in software engineering is presented in this document. Information about AI and its varieties can be found here. A sneak peek at AI agents, learning in AI, and subsets of AI will also be included.